THE PHENOMENON OF CRYPTOCURRENCY FROM DIVERSE PERSPECTIVES - Živilė Nemickienė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose, 2019)
The growth of crypto industry develops vigorous, especially in recent years, moving from a universally controlled electronic cash system society to complete financial freedom. Given all the failures, the phenomenon, though treated controversially by politicians and financial authorities all around the world, slowly moves towards standardization. The global law-making chaos is temporary. People, private individuals or corporations, on the contrary, have firm confidence in a chance to handle personal money without all-seeing intermediators who track their total spending. People are ready to battle for the currency, which does not require the owner’s identity or a central server and overt control of banks and governments over the monetary transactions. The crypto industry matured at an incredible pace offers this possibility and firmly takes roots in a global society. The phenomenon of cryptocurrency affects social aspects, starting various debates about the phenomenon itself, cultural changes caused by it, political-economic decisions, bans, or even revolutions all over the world. Money reveals what kind of society we are giving us power and confidence and then society gives different meanings to faceless money. The fashion for crypto entered the artistic layers. Crypto money evokes the phenomenon of social exchange, which leads to the effect of social subjects’ interaction, and the allocation of power inside a social structure. The aim of the study is to discuss these aspects. The analysis of articles, news portals, and social media posts related to cryptocurrency and blockchain technologies proofs the manifestation of the stated aspects. All the aspects of the phenomenon that take an active part in our lives today will undoubtedly leave a significant trace in history. The particular observable behaviour, such as successful moneymaking, encourage novices to started imitating experts because the interaction between the individual and the situation determines the outcome.